2015
DOI: 10.3389/fpsyg.2015.01044
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent effects on tasks assessing reinforcement learning and interference inhibition

Abstract: Increasing evidence suggests that the prefrontal cortex (PFC) is influenced by sex steroids and that some cognitive functions dependent on the PFC may be sexually differentiated in humans. Past work has identified a male advantage on certain complex reinforcement learning tasks, but it is unclear which latent task components are important to elicit the sex difference. The objective of the current study was to investigate whether there are sex differences on measures of response inhibition and valenced feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
35
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 80 publications
(117 reference statements)
10
35
5
Order By: Relevance
“…Sex differences were absent in the numbers of trials to acquire the reversals, as well as in response latencies and accuracy on the DR task. This is in contrast to a few humans studies, which reported a male advantage for Reversal Learning in children (Overman 2004) and adults (Evans and Hampson 2015a, b) and a female advantage in working memory (Duff and Hampson 2001). Interestingly, Duff and Hampson (2001) also found a female advantage in the time to complete the task.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Sex differences were absent in the numbers of trials to acquire the reversals, as well as in response latencies and accuracy on the DR task. This is in contrast to a few humans studies, which reported a male advantage for Reversal Learning in children (Overman 2004) and adults (Evans and Hampson 2015a, b) and a female advantage in working memory (Duff and Hampson 2001). Interestingly, Duff and Hampson (2001) also found a female advantage in the time to complete the task.…”
Section: Discussioncontrasting
confidence: 99%
“…There is also growing evidence for sex differences in certain prefrontal (PFC)-dependent tasks. For example, the Iowa gambling task (IGT), in which participants must chose cards from the advantageous decks in order to amass a maximal number of points, tends to yield a male advantage (Evans and Hampson 2015a; van den Bos et al 2013). Conversely, women tend to outperform men on other spatial tasks (memory for object location), as well as tasks of verbal fluency, verbal memory (Hampson 2002) and episodic memory (Herlitz 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women compared to men tended to pick decks with lower frequency of punishment on a gambling task (31). In a study combining electroencephalography (EEG) and a guessing task with reward (or punishment) feedback, boys showed lower feedback-related negativity (FRN) and less changes in post-punishment behavior (32).…”
Section: Sex Differences In Reward and Punishment Processingmentioning
confidence: 99%
“…In contrast, females appear to be advantaged in working memory tasks that emphasize monitoring and updating [40,41]. Other tasks that require inhibitory control such as the Stroop color-word task or the Stop-Signal Task have usually failed to find sex differences in performance (e.g., [42][43][44]), even though sex differences may be observed in brain activation patterns [43].…”
Section: Introductionmentioning
confidence: 99%